(untitled) (Veterinary Science, 2022)
The objective of this study was to determine the presence antibodies of Brucella suis and of Aujeszky’s Disease Virus in swine herds located in peri-urban limits of Uriburu (La Pampa). A total of 290 breeding animals from 31 swine farmers were serologically sampled. For the detection of agents against Brucellosis, the serum lot was processed by the agglutination technique with Buffered Plate Antigen (BPA) and Fluorescent Polarization (FPA) according to Nielsen et al.,1999. For Aujeszky’s Disease Virus, a commercial blocking ELISA kit was used for the detection of specific antibodies from Aujeszky’s Disease Virus glycoprotein E (CIVTEST — Laboratorios HIPRA S. A, Girona, Spain). Only 1.03% of sampled animals resulted positive for Brucella suis distributed in 3 farms (9.7%). On the other hand, 16 positive cases for Aujeszky’s Disease Virus (5.52%) were detected in 8 farms (25.8%). Only 2 farms share positive cases for Brucella suis and Aujeszky’s Disease Virus, which reduces to 9 farms (29%) that have been affected by either of these two diseases. Due to the relevant information obtained, the need to continue with the research is highlighted, expanding the sampling to other towns within La Pampa province as well as to determine the presence of other etiological agents.